Narrative construction in Labid's poetry (Journal of the College of Basic Education, 2023)
Pre-Islamic poetry represents the pinnacle of Arabic literature for its central position in Arab culture and for the abundance of its material and its eloquence. Hence, the study of this literature was a modern mechanism in which there is some adventure, because the researcher must work to harmonize between the mechanisms of the study and its material, without prejudice to both. On this basis, our research seeks to An attempt to reveal the narrative structure in Lapid's poetry, and before that we must clarify a point that we consider important here, which is that the word (narration and narratives) is one of the modern terms that appeared at the hands of (Tzvetan Todorov) in 1969, and the narrative led to the emergence of two currents: the first is narrative The semantics that means the content of the actions, without caring about the narration that creates them, the semantics that means the content of the acts, and without caring about the narration that creates them, but with the logic that governs the succession of those actions. Visions, and relationships between the narrator and the narrator (). And narration, as Roland Barthes sees it, is an act that is difficult to comprehend. ( ), that the foregoing, in short, is an overview of the narration from the Western view, but if we examine our Arabic books, we will find the word narration mentioned in the sense of weaving, then narrating - a shield (musrad) and (musradah) with emphasis, so it was said that its narration is woven, which is the overlapping of the throats, some of them in each other, and so and so (to list) The hadeeth if it has a good context for it () and the word narration came in the Almighty’s saying ((to do righteous deeds and predestination in narration, and do righteous deeds. Indeed, I see what you do)) () Surat Saba / verse 11, from here we can say that the word is present in our Arabic language deep In ancient times, however, the West has shed light on it in a strong way and in many and complex details, while we can simply say that narration in our language means the overlapping of the links with each other, i.e. the tightness of their weaving, and we have tried to mix the Western vision